[Composite panorama from the hills behind the dorms] (1987)
View of campus and the surrounding fields on a clear day from the site of the future Cerro Vista apartments. The aeronautics hangar, Facilities, Kennedy Library, Fisher Science, and the North Mountain dorms are all easily identifiable. Digitally created from a composite of several photographs.